Issue convergence and issue divergence in the content of television campaign messages in two-round presidential systems: Chile, 2005–2017 - Leiva, Andrés; Lisbona, Francisca; Navia, Patricio; Cabezas, José Miguel (Frontiers in Political Science, 2025)
Issue convergence theories posit that, in a two-person race, the messages of the candidates converge to the same priorities. Conversely, issue ownership theory argues that candidates will emphasize issues where they, or their parties, hold a reputational edge. In multi-candidate, two-round presidential elections, the first-round campaign normally allows for greater issue divergence. However, in the runoff campaigns, the two candidates should be more likely to converge on the issues. Through content analysis of television ads, this study examines four Chilean presidential election campaigns from 2005 to 2017. Employing a regression discontinuity design (RDD), we explore if candidates converged on the issues mentioned in their campaign messages in the runoff compared to the first round. The findings indicate that right-wing candidates more frequently address crime, pensions, and employment, whereas left-wing candidates focus more on education during the first-round campaign. In the runoff, we find convergence on campaign messages on education and pensions, but in other issues, the candidates’ messages continue to show divergence.